Intellectual Structure of the Research on Corporate Foresight and Innovation: Thinking inside the Box - Garcia-Lillo, Francisco; Seva-Larrosa, Pedro (Transformations In Business & Economics, 2025)
The aim of this study is to identify the scholarly works that have had the greatest impact on the research on corporate foresight (CF) and innovation and to analyze the intellectual structure of the knowledge base of the research developed in this field. The methodology is based on the bibliometric techniques of citation and co-citation analysis, which are applied to a total of 129 articles published between 2006 and 2023* (database consultation date: January 3, 2024). Clarivate Analytics' Web of Science™ (WoS) database is used in this study. We chose bibliometric analysis over other traditional methods like systematic literature review (SLR) as bibliometric techniques are replicable, objective, unbiased, and rigorous, and thus superior to other techniques for conducting literature reviews.